IMPLEMENTATION OF AGGREGATE PLANNING FOR SMES IN THE MANUFACTURING INDUSTRY - Sarjono, Haryadi (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2025)
This study aims to examine the use of aggregate planning methods in micro, small, and medium enterprises (MSMEs) operating in the aluminum industry within the Greater Jakarta (Jabodetabek) region. It addresses the lack of structured aggregate planning practices in these enterprises and introduces an illustrative framework for evaluating labor control strategies. A heuristic approach is applied to compare cost estimations under three different aggregate planning methods: Permanent Workforce Control, Subcontract Control, and Hiring and Layoffs Control. Four MSMEs were selected as case study subjects, and cost-based simulations were conducted to demonstrate the potential impact of each method. The analysis reveals comparative outcomes of each method across the four case studies. While specific results are not detailed here, the study provides a practical view of cost variations associated with each planning strategy. The study is limited to illustrative simulation based on four MSMEs in a single industrial sector and region. Further empirical validation is recommended. The study serves as a preliminary reference for MSMEs to assess the suitability of different workforce planning approaches in response to fluctuating production demands.